Effectiveness Test of White Skin Extract Cream from Red Watermelon (Citrullus Lanatus) on Increasing Elasticity, Sebum and Hydration in White Mice (Mus Musculus) Skin - Farida SR Simamora; Janice Janice; Widya Pasca Amir (International Journal of Health and Pharmaceutical (IJHP), 2023)
Skin moisturizing gel can provide a moisturizing effect on the skin. One of the natural ingredients that can be made into gel preparations is the white peel of watermelon (Citrullus Lanatus) because it contains a lot of citrulline, vitamin A, vitamin B2, vitamin B6, vitamin E, vitamin C, and protein, beta-carotene, lycopene, and water. The purpose of this study was to determine the activity of the ethanol extract of watermelon rind on increasing elasticity, sebum, and hydration in the skin of male white mice. This study used the Pretest-Posttest Control Group Design method. The stages of the research were sample collection, extraction, formulation of various concentrations of moisturizing gel preparations (0, 2.5%, 5%, and 10%). Tests were carried out on the skin of male mice for 4 weeks by measuring levels of elasticity, sebum, and hydration. The results of the phytochemical screening extracts contained flavonoids, saponins, steroids, triterpenoids, and glycosides. The evaluation results showed that all formulas met good preparation parameters and did not irritate the skin. The measurement results in the fourth week of each cream preparation group showed an increase in the levels of elasticity, sebum and hydration and differed significantly from the blank group (p <0.05) and the highest increase occurred in cream with watermelon rind extract concentration 10 %. The results of this study indicate that the cream preparation of ethanol extract of watermelon rind can increase the levels of elasticity, sebum, and hydration of the skin.